Los castros del occidente de la provincia de Cáceres - Martín Bravo, Ana Mª (Complutum, 1994)
This paper is concerned with the study of the features of the Iron Age settlementsin the west area of the province of Cáceres (SW Spain). The Late Bronce Age sites very seldom reimained inhabited during the Early Iron Age. Those site were mostly replaced by other, wich follow the tradition of small-sized, difficult of access, located at the top. although they star being walled. Together with these, there was other kind of less relevant defenselless settlements located at the plains. During the Iron Agen, from late 5th century B. C., the settlements withdraw to the most uneven bants of the river and are rearranged in concentrated, bigger hillforts. Nevertheless, they do not reach by any means the same development as the urban population centres both in the South Bark of the River Tajo and in Avila and Salamanca.
Keywords: Cáceres; Hill-forts; Settlement pattern; Early Iron Age; Iron Age